Redox Transformations of Iron at Extremely Low pH: Fundamental and Applied Aspects - Johnson, D. Barrie; Kanao, Tadayoshi; Hedrich, Sabrina (Frontiers in Microbiology, 2012)
Many different species of acidophilic prokaryotes, widely distributed within the domains Bacteria and Archaea, can catalyze the dissimilatory oxidation of ferrous iron or reduction of ferric iron, or can do both. Microbially-mediated cycling of iron in extremely acidic environments (pH <3) is strongly influenced by the enhanced chemical stability of ferrous iron and far greater solubility of ferric iron under such conditions. Cycling of iron has been demonstrated in vitro using both pure and mixed cultures of acidophiles, and there is considerable evidence that active cycling of iron occurs in acid mine drainage streams, pit lakes and iron-rich acidic rivers, such as the Rio Tinto. Measurements of specific rates of iron oxidation and reduction by acidophilic microorganisms show that different species vary in their capacities for iron oxido-reduction, and that this is influenced by the electron donor provided and growth conditions used. These measurements, and comparison with corresponding data for oxidation of reduced sulfur compounds, also help explain why ferrous iron is usually used preferentially as an electron donor by acidophiles that can oxidize both iron and sulfur, even though the energy yield from oxidizing iron is much smaller than that available from sulfur oxidation. Iron-oxidizing acidophiles have been used in biomining (a technology that harness their abilities to accelerate the oxidative dissolution of sulfidic minerals and thereby facilitate the extraction of precious and base metals) for several decades. More recently they have also been used to simultaneously remediate iron-contaminated surface and ground-waters and produce a useful mineral by-product (schwertmannite). Bioprocessing of oxidized mineral ores using acidophiles that bring about the reductive dissolution of ferric iron minerals such as goethite has also recently been demonstrated, and new biomining technologies based on this approach are being developed.